Characteristics Study of Daily Soil Cover in Pulau Burung Landfill, Penang - Mohamad, Maheera; Osman, Nor Hasni; Abdul Rahim, Mohd Kamarul Irwan; Abustan, Ismail; Mohd Arif Zainol, Mohd Remy Rozainy; Samuding, Kamarudin; Zakaria, Siti Nor Farhana; Abu, Falah (Trans Tech Publications Ltd, 2022)
Municipal solid waste landfills are major sources of environmental pollution. This study evaluated heavy metal concentrations in soils around Pulau Burung Landfill, Penang, Malaysia, to determine the pollution potential of a landfill. Soil samples were collected at depths of 0–20 cm (top), 20–40 cm (center) and 40–60 cm (bottom) around the landfill and at a control site and characterized for various properties and concentrations of Lead (Pb) and Zinc (Zn). Samples of daily soil cover, collected from the same sites where soil samples were collected, were also analyzed for several of heavy metals analysis. The soils were silty sand, mostly acidic (4.45) with low organic matter content (0.41%) and cation exchange capacity (3.15-3.19 meq/100 g). Other basic physico-chemical and adsorption properties were conducted on soil indicated that soil alone is not effective to be used in the landfill to support the pollutant for a long time. Heavy metals concentrations (as background data) in the soils followed the order Iron (Fe) > Zinc (Zn) > Manganese (Mn) > Lead (Pb) > Arsenic (As) > Chromium (Cr) > Cadmium (Cd) > Copper (Cu) > Nickle (Ni) with samples from around the landfill having higher concentrations especially Iron, (Fe) and Zinc, (Zn). For soil profile contribution, heavy metal enrichment was highest at a depth of 40–60 cm. In short, soil alone cannot retain and minimize the migration of heavy metals in landfill based on the results of this study including removal efficiency test. Monitoring of environments around active landfills needs to be ongoing to mitigate negative impacts on humans and the environment